An Enhanced Framework for Object-Relational Database Design - An Experimental Study - Bohalfaya, Huda M.; Elakeili, Salwa M.; Abdelnabi, Esra A.; Maatuk, Abdelsalam A. (2024 International Symposium of Systems, Advanced Technologies and Knowledge (ISSATK), 2024)
Object-relational conceptual modeling tools do not support all new concepts available in SQL4. This study presents an enhanced empirical research framework for object-relational database design based on conceptual modeling. This paper describes a proposal for heuristic rules for designing an object-relational database and translating data and relationship semantics from the conceptual schema generated by a UML class diagram to its logical schema counterpart by SQL:2008. A set of rules has been proposed that help visualize and implement object-relational databases, allowing the user to create a script model of a database using SQL. The study explains the importance of these guidelines and gives a detailed explanation of the proposed rules with an illustrative example. The proposed method was evaluated by applying it to a case study and comparing the results with other methods and proposals. This study confirms that modern technologies and new databases play an important role in the success of software design, so it attempts to facilitate the design process and help software developers understand this type of database and save them time and effort.